2018
DOI: 10.1042/bsr20171140
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between MBL2/CD14/TNF-α gene polymorphisms and susceptibility to spinal tuberculosis in Chinese population

Abstract: Objective: The present study investigated the clinical significance of mannose-binding lectin 2 (MBL2), cluster of differentiation 14 (CD14) and tumour necrosis factor-α (TNF-α) gene polymorphisms in patients with spinal tuberculosis (TB) in Chinese population. Methods: A total of 240 patients with spinal TB were enrolled in the present study from May 2013 to August 2016 at Hangzhou Red Cross Hospital. A total of 150 age- and sex-matched healthy subjects were enrolled as controls. The genomic DNA was extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Also, analyzes of odds ratio (OR) revealed an increased risk of TB when this allele was present, in case of both pulmonary and extrapulmonary disease. Of note, three of such studies [21][22][23] reported this aforementioned association in Chinese participants, reinforcing the idea that this CD14 allele may indeed increase the risk of developing TB in this particular population.…”
Section: Cd14 Polymorphisms and Risk Of Tuberculosismentioning
confidence: 53%
See 3 more Smart Citations
“…Also, analyzes of odds ratio (OR) revealed an increased risk of TB when this allele was present, in case of both pulmonary and extrapulmonary disease. Of note, three of such studies [21][22][23] reported this aforementioned association in Chinese participants, reinforcing the idea that this CD14 allele may indeed increase the risk of developing TB in this particular population.…”
Section: Cd14 Polymorphisms and Risk Of Tuberculosismentioning
confidence: 53%
“…1). Through the study selection process, 13 articles met the inclusion criteria and were included in the systematic review [3,9,[21][22][23][24][25][26][27][28][29][30][31]. The majority of the studies evaluated CD14 gene polymorphisms (n = 9), whereas four studies analyzed NOD2 polymorphisms.…”
Section: Selection Of Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned in the literature, GA genotype of SNP rs2069837 A>G located within IL‐6 was associated with PTB, while GG genotype did not show any association with TB (Wu et al, ). Prior studies have noted the relationship between CT genotype of TNF‐857 and spinal TB, while TT genotype did not correlate with spinal TB (Zheng et al, ). Our research shows that heterozygous genotypes are meaningful; however, a number of studies have shown a significant evidence of homozygosity.…”
Section: Discussionmentioning
confidence: 89%